2017
DOI: 10.1249/jes.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Autophagy in Fatty Liver Disease

Abstract: Hepatic steatosis prevails each year. Autophagy is integral in mitochondrial quality control and lipid homeostasis in the liver. No pharmacological strategies are currently available to reduce hepatic steatosis, but exercise has been known to improve clinical outcomes of chronic liver disease, particularly non-alcoholic fatty liver disease (NAFLD). Recent studies suggest that exercise may improve NAFLD through enhancing autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
1
23
0
1
Order By: Relevance
“…In this study, we found that MAP1LC3A a marker of lipophagy, lipid specific autophagy, is dramatically downregulated in over-nutrition induced NAFLD liquid crystal hepatic lipid droplet accumulation. As exercise can improve lipid over accumulation by increasing lipophagy [49,50], the next step is to investigate whether exercise can reactivate MAP1LC3A associated autophagy. Understanding the relationship between liquid crystal hepatic lipid droplets and the MAP1LC3A autophagy could provide a unique prospective towards understanding, preventing, and treating NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that MAP1LC3A a marker of lipophagy, lipid specific autophagy, is dramatically downregulated in over-nutrition induced NAFLD liquid crystal hepatic lipid droplet accumulation. As exercise can improve lipid over accumulation by increasing lipophagy [49,50], the next step is to investigate whether exercise can reactivate MAP1LC3A associated autophagy. Understanding the relationship between liquid crystal hepatic lipid droplets and the MAP1LC3A autophagy could provide a unique prospective towards understanding, preventing, and treating NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is also used by H. pylori to survive 78,79 CD Defect/ active MAP1S, NOD2, CLEC12A, ATG16L, NDP52, IRGM NOD2 direct ATG16L1 on the plasma membrane and initiate autophagy. Onset of CD is triggered by dysfunction of autophagy [80][81][82] Fatty liver disease Defect SREBP-2, PNPLA8, FGF21 Impairment of autophagy decreases insulin resistance and enhances oxidative stress and deteriorates hepatocyte damage [83][84][85] Alcoholic liver disease Defect CNR2, ATG5…”
Section: Becn1 Cftrmentioning
confidence: 99%
“…In the accompanying review by Chun et al (4), the mechanisms by which exercise benefits NAFLD has focused primarily on autophagy. Extensive preclinical and consistent but very limited data in patients with NAFL suggest impaired hepatic autophagy in NAFLD.…”
mentioning
confidence: 99%
“…Exercise is an effective non-pharmacological intervention that promotes improvement of liver function tests in NAFLD and in the accompanying article, the thesis is that exercise is beneficial through enhanced autophagy in the skeletal muscle and possibly liver. The mechanisms by which exercise stimulates hepatic autophagy are currently areas of active investigation as mentioned in the article by Chun et al (4). There is emerging evidence that exercise induced secretion of irisin and potentially other myokines promote browning of fat and may have direct effects on hepatocyte triglyceride accumulation (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation